Comparative analyses of complete chloroplast genomes reveal interspecific difference and intraspecific variation of Tripterygium genus - Xu, Kai-Ling; Zhang, Zhong-Mou; Fang, Wen-Liang; Wang, Ya-Dan; Jin, Hong-Yu; Wei, Feng; Ma, Shuang-Cheng (Frontiers in Plant Science, 2024)
The genus Triperygium was of great medicinal value and attracted much attention on the taxonomic study using morphological and molecular methods. In this study, we assembled twelve chloroplast genomes of Tripterygium to reveal interspecific difference and intraspecific variation. The sequence length (156692 -157061 bp) and structure of Triperygium were conserved. Comparative analyses presented abundant variable regions for further study. Meanwhile, we determined the ndhB gene under positive selection through adaptive evolution analysis. And the phylogenetic analyses based on 15 chloroplast genomes supported the monophyly of Tripterygium hypoglaucum and the potential sister relationship between Tripterygium wilfordii and Tripterygium regelii. Molecular dating analysis indicated the divergence time within Triperygium was around 5.99 Ma (95% HPD = 3.11 -8.68 Ma). The results in our study provided new insights into the taxonomy, evolution process and phylogenetic construction of Triperygium using complete plastid genomes.